2013
DOI: 10.1161/circep.112.970459
|View full text |Cite|
|
Sign up to set email alerts
|

Prophylactic Radiofrequency Ablation in Asymptomatic Patients With Wolff–Parkinson–White Is Not Yet a Good Strategy

Abstract: Background— Therapeutic management of asymptomatic patients with a Wolff–Parkinson–White (WPW) pattern is controversial. We compared the risk:benefit ratios between prophylactic radiofrequency ablation and no treatment in asymptomatic patients with WPW. Methods and Results— Decision analysis software was used to construct a risk–benefit decision tree. The target population consisted of 20- to 40-year-old asymptomatic patients with WPW without structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
0
15
0
4
Order By: Relevance
“…Secondly, patients may have a strong preference for taking the small but one-off risk of ablation, rather than the small but indefinite risk of SCD. Thirdly, the presence of pre-excitation on the ECG may bar people from certain activities, for example professional flying or competitive sport (Chevalier et al, 2013;Link, 2009). Finally, the location of the pathway must be considered.…”
Section: Asymptomatic Pre-excitationmentioning
confidence: 99%
“…Secondly, patients may have a strong preference for taking the small but one-off risk of ablation, rather than the small but indefinite risk of SCD. Thirdly, the presence of pre-excitation on the ECG may bar people from certain activities, for example professional flying or competitive sport (Chevalier et al, 2013;Link, 2009). Finally, the location of the pathway must be considered.…”
Section: Asymptomatic Pre-excitationmentioning
confidence: 99%
“…This may change pathway properties and our ability to interpret the conduction velocity of an accessory pathway in the anesthetized state is not clear. Multiple studies in adults and children have demonstrated that isoproterenol can enhance accessory pathway conduction [4,[20][21][22]. In the pediatric population, Moore et al [20] demonstrated that the addition of isoproterenol increased the percentage of children deemed "high risk" at EPS from 5% to 25%.…”
Section: Role Of Isoproterenol Testingmentioning
confidence: 99%
“…The combination of new data suggesting a significantly increased risk of life-threatening events than previously described coupled with the widespread use of ablation as a safe and effective treatment tool have made WPW one of the most common indications for invasive EP testing and ablation in young people [1]. While there is little argument or disagreement over the management of the symptomatic young patient with WPW, there are still divergent views on the assessment and management of the asymptomatic patient [2][3][4][5]. In light of the new guidelines on the management of the young patient with ventricular preexcitation [6], some have questioned whether we have gone too far on the side of aggressive intervention in the evaluation of the asymptomatic patient with pre-excitation.…”
Section: Introductionmentioning
confidence: 99%
“…A low WPW prevalence in the population is also a barrier to cost-effectiveness. 2 As highlighted by many publications, risk factors for identifying the truly high-risk patient lack accuracy. However, the identification of factors generally associated with a favorable long-term outcome is somewhat easier.…”
Section: Circulationmentioning
confidence: 99%